2020
DOI: 10.1186/s12870-020-02552-8
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ protein profile analysis of sugar beet under salt stress: different coping mechanisms in leaves and roots

Abstract: Background: Salinity is one of the most serious threats to world agriculture. An important sugar-yielding crop sugar beet, which shows some tolerance to salt via a mechanism that is poorly understood. Proteomics data can provide important clues that can contribute to finally understand this mechanism. Results: Differentially abundant proteins (DAPs) in sugar beet under salt stress treatment were identified in leaves (70 DAPs) and roots (76 DAPs). Functions of these DAPs were predicted, and included metabolism … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 75 publications
1
11
1
Order By: Relevance
“…Indeed, we found that basic blue protein (Bv1_023200_jmkt.t1) and uclacyanin-2 (Bv6_144730_qgsa.t1) were down-regulated by the mtr-MIR408-p3_2ss18GT19GA-mediated ceRNA network (Figure 8), which may be related to copper distribution. This is in agreement with our previous studies on the proteome of sugar beet under salt stress revealing up-regulation of plastocyanin in leaves [48], consistent with copper ions being preferentially supplied to photosynthesis. Other studies have shown that the expression of miR408 was up-regulated under abiotic stress in Arabidopsis thaliana [49] and that the overexpression of miR408 enhanced drought tolerance in chickpea (Cicer arietinum L.) [50].…”
Section: Analysis Of Salt Stress Response In Sugar Beet Leavessupporting
confidence: 93%
“…Indeed, we found that basic blue protein (Bv1_023200_jmkt.t1) and uclacyanin-2 (Bv6_144730_qgsa.t1) were down-regulated by the mtr-MIR408-p3_2ss18GT19GA-mediated ceRNA network (Figure 8), which may be related to copper distribution. This is in agreement with our previous studies on the proteome of sugar beet under salt stress revealing up-regulation of plastocyanin in leaves [48], consistent with copper ions being preferentially supplied to photosynthesis. Other studies have shown that the expression of miR408 was up-regulated under abiotic stress in Arabidopsis thaliana [49] and that the overexpression of miR408 enhanced drought tolerance in chickpea (Cicer arietinum L.) [50].…”
Section: Analysis Of Salt Stress Response In Sugar Beet Leavessupporting
confidence: 93%
“…Liu et al (2020) reported that the reduction of sucrose in roots might be due to the decomposition of sucrose into other soluble sugars and increments of tricarboxylic acid (TCA) cycle activity under stress [50]. Recently, sucrose synthases (SuSy), which take part in sucrose synthesis and decomposition in plants, have been found to be accumulated in sugar beet roots under salt stress, suggesting that osmotic regulation in roots may be related to the accumulation of these enzymes [53].…”
Section: Osmotic Adjustment Through Accumulation Of Compatible Solutesmentioning
confidence: 99%
“…So far, chlorophyll content, photosynthetic rate, and CO 2 assimilation have been used as selection criteria in beets [18,19,34,40,53], as it is known that stress conditions damage the most stress-sensitive organelles (chloroplasts) and impact PSII activity and CO 2 assimilation rate negatively [154]. In sugar beet, the decrease in chlorophyll levels caused by stress might be related to ROS production and osmotic stress, leading to pigment degradation, decrease in CO 2 influx, and photosynthesis [40].…”
Section: Selection Of Salt-and Drought-tolerant Beets Based On Different Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Ocimum basilicum L., the obvious effect of drought stress on phenylpropanoid biosynthesis increases the content of methyl tea phenol and methyl eugenol and then alters the expression profiles of leaves ( Mandoulakani et al, 2017 ). Salt stress may regulate the synthesis of the proteins related to carbohydrates, detoxification, antioxidation, secondary metabolism, and ion transport ( Rahman et al, 2015 ; Xiong et al, 2017 ; Li J. L. et al, 2020 ) that can enhance plant salt tolerance and subsequently improve growth performance ( Zhao C. Z. et al, 2019 ). Other stress factors, such as pathogens and pollutants, may also lead to the overexpression of some proteins, thus changing the tolerance and external performance of plants ( Feng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%